Efficient utilization of photoelectron-hole at semiconductor-microbe interface for pyridine degradation with assistance of external electric field - Hefei Shi; Wenbo Fan; Xinbai Jiang; Dan Chen; Cheng Hou; Yixuan Wang; Yang Mu; Jinyou Shen (Water Research X, 2024)
In this study, enhanced pyridine bio-photodegradation with assistance of electricity was achieved. Meanwhile, photoelectron-hole played a vital role in accelerating pyridine biomineralization. The significant separation of photoelectron-hole was achieved with an external electric field, which provided sufficient electron donors and acceptors for pyridine biodegradation. The enhanced electron transport system activity also revealed the full utilization of photoelectron-hole by microbes at semiconductor-microbe interface with assistance of electricity. Microbial community analysis confirmed the enrichment of functional species related to pyridine biodegradation and electron transfer. Microbial function analysis and microbial co-occurrence networks analysis indicated that upregulated functional genes and positive interactions of different species were the important reasons for enhanced pyridine bio-photodegradation with external electric field. A possible mechanism of enhanced pyridine biodegradation was proposed, i.e., more photoelectrons and holes of semiconductors were utilized by microbes to accelerate reduction and oxidation of pyridine with the assistance of electrical stimulation. The excellent performance of the photoelectrical biodegradation system showed a potential alternative for recalcitrant organic wastewater treatment.